Performance of AnMBR in Treatment of Post-consumer Food Waste: Effect of Hydraulic Retention Time and Organic Loading Rate on Biogas Production and Membrane Fouling - Ariunbaatar, Javkhlan; Bair, Robert; Ozcan, Onur; Ravishankar, Harish; Esposito, Giovanni; Lens, Piet N. L.; Yeh, Daniel H. (Frontiers in Bioengineering and Biotechnology, 2021)
Anaerobic digestion of food waste (FW) is typically limited to large reactors due to high hydraulic retention times (HRTs). Technologies such as anaerobic membrane reactors (AnMBRs) can perform anaerobic digestion at lower HRTs while maintaining high chemical oxygen demand (COD) removal efficiencies. This study evaluated the effect of HRT and organic loading rate (OLR) on the stability and performance of a side-stream AnMBR in treating diluted fresh food waste (FW). The reactor was fed with synthetic FW at an influent concentration of 8.24 (± 0.12) g COD/L. The OLR was increased by reducing the HRT from 20 d to 1 d. The AnMBR obtained an overall removal efficiency of > 97% and > 98% of the influent COD and total suspended solids (TSS), respectively, throughout the course of operation. The biological process was able to convert 76% of the influent COD into biogas with 70% methane content, while the cake layer formed on the membrane gave an additional COD removal of 7%. Total ammoniacal nitrogen (TAN) and total nitrogen (TN) concentrations were found to be higher in the bioreactor than in the influent, and average overall removal efficiencies of 17.3 (± 5) % and 61.5 (± 3) % of TAN and TN, respectively, were observed with respect to the bioreactor concentrations after 2 weeks. Total phosphorus (TP) had an average removal efficiency of 40.39 (± 5) % with respect to the influent. Membrane fouling was observed when the HRT was decreased from 7 to 5 d and was alleviated through backwashing. This study suggests that the side-stream AnMBR can be used to successfully reduce the typical HRT of wet anaerobic food waste (solids content 7%) digesters from 20 days to 1 day, while maintaining a high COD removal efficiency and biogas production.